STRATEGI PEMBELAJARAN DALAM MENUMBUHKEMBANGKAN DISIPLIN ANAK USIA 5-6 TAHUN DI TK MUJAHIDIN 1 PONTIANAK - Ningrum, Dewi Lestari; Chiar, Chiar; Marmawi, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the lack of learning strategies undertaken by teachers in developing the character of childrenâ€™s discipline so that there are still many children who lack discipline. The general problem of this research is how is the learning strategy in developing the discipline character of children in kindergarten Mujahidin 1 Pontianak? The purpose of this study is to describe learning strategies in developing discipline character. The assessment aspect of the learning strategy of developing discipline character is that the teacher uses communication skill in children and clarifies values to develop the character of discipline. This research uses descriptive qualitative research. The research subjects were 12 teachers in class B. the location of the study was Pontianak Mujahidin 1 kindergarten. Based on the results of the sudy concluded as follows 1. Develop character discipline in children, namely verbal communication. 2. The value clarification strategy used by the teacher in developing the character of discipline in children is the teacher accustoming the child to finding, deciding and taking his own attitude about discipline. 3. Supporting factors in fostering the character of discipline in children are means from schools that support to foster the character of child discipline, and are supported by teacher who accustom children to discipline. While the inhibiting factor is from associate friends, if there are children who are not discipline or break the rules, there are other children who copy. Â Keywords: Learning Strategies, Discipline Character.